Training on Milkfish Processing to Enhance the Knowledge of Tambak Asri Surabaya Community in Fish Crackers Production - Izza Anshory; Indah Sulistiyowati; Lukman Hudi; Muh Arul Romadhon; Hariska Ade Pratama (Universitas Muhammadiyah Sidoarjo, 2023)
Tambak Asri Village, which is located in Morokrembangan Village, Surabaya City, some of its people have problems in community welfare. The purpose of this community service activity is to improve community welfare through providing knowledge about making milkfish crackers. The method used in this community service activity is divided into two stages. The first stage is to communicate with abdimas partners regarding fish crackers making activities. The second stage is to explain the formulation and processing of milkfish into cracker products. The result of this community service activity is the increase in knowledge of how to process milkfish into fish crackers products. Highlights: Enhanced welfare: The community service activity aims to improve the welfare of Tambak Asri Village residents through knowledge sharing on milkfish cracker production. Two-stage method: The activity involves communication with abdimas partners and providing explanations on the formulation and processing of milkfish for cracker production. Increased knowledge: The outcome of the community service activity is an increased understanding among participants on how to process milkfish into fish cracker products. Keywords: Tambak Asri, Surabaya, community welfare, milkfish crackers, knowledge